Status and impact of commercial agroforestry in India - Dhiman, R.C. (Indian Journal of Agroforestry, 2020)
Commercial agroforestry- the practice of growing trees as cash crops with intercropsis now happening in many parts of the country. Numerous agencies in private and government sectors are promoting and helping in sustaining the practice with supply of quality planting stock, technical know-how in tree culture and intercrops, procuring/purchasing tree produce, providing need based extension support, developing new productive site matched cultivars and cultural inputs related therewith. Commercial agroforestry, in India, is estimated to be presently practiced over 5 million ha with tree species belonging to Eucalyptus, Populus, Casuarina, Leucaena, Ailanthus, Melia, Anthocephalus, Acacia, Leucasena, Bombax etc. genera.The practice is estimated to produce 100 million m3 timber/pulpwood for industrial and domestic use and 150 million tonne firewood, add approximately 15 million tonne organic matter through leaf fall, sequester 60 million tonne carbon annually in tree components (excluding in soil and that locked in the wood products), generate employment of 4000 million person days/annum in nursery and plantation activities. The value of wood/pulpwood produced is estimated to be around Rs. 10000 billion and that of firewood as Rs. 30000 million annually. The activity is likely to stay in view of the chronical shortage of wood faced in the country and its economical edge over the traditional agriculture.